JCER 2019
DOI: 10.30950/jcer.v15i1.1018
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Generic Skills Development in a Bachelor European Studies

Abstract: To ensure a smooth transition from studies to professional careers, students' skills and attitudes are often considered of greater value than theoretical knowledge and understanding. Yet, whereas typical academic skills such as research and writing are commonly monitored and trained, generic skills such as teamwork and communication receive scant attention. At Maastricht University, we developed a portfolio to raise awareness about skills required to take full advantage of the Problem-Based Learning environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
0
12
0
5
Order By: Relevance
“…Research has shown that the politics/IR curricula in the UK provides students with a range of transferable skills that they will find of great use as they move towards employment, the discipline is poor in highlighting this: 'if we don't tell students what we are teaching them, then they won't realise that they have gained a whole range of skills through their study of politics' (see Clark and Martin 2016). An obvious way to ensure all students engage with the skill development aspect of this agenda is to embed and assess the skills via the choice of assessment (Curtis 2013) and across the curricula (Adriaensen et al 2019). Yet it is clear that essay writing is the most common form of assessment (Deardorff et al 2009;Blair and McGinty 2012) and whilst it is clear essay writing allows students to develop a range of transferable skills, the need to ensure students can demonstrate the full range of skills demands a broader range of assessment tasks.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that the politics/IR curricula in the UK provides students with a range of transferable skills that they will find of great use as they move towards employment, the discipline is poor in highlighting this: 'if we don't tell students what we are teaching them, then they won't realise that they have gained a whole range of skills through their study of politics' (see Clark and Martin 2016). An obvious way to ensure all students engage with the skill development aspect of this agenda is to embed and assess the skills via the choice of assessment (Curtis 2013) and across the curricula (Adriaensen et al 2019). Yet it is clear that essay writing is the most common form of assessment (Deardorff et al 2009;Blair and McGinty 2012) and whilst it is clear essay writing allows students to develop a range of transferable skills, the need to ensure students can demonstrate the full range of skills demands a broader range of assessment tasks.…”
Section: Contextmentioning
confidence: 99%
“…Clearly managing multiple deadlines is an essential skill in most forms of employment as is prioritizing tasks but is there enough space in the curriculum to explain this aspect of skills development? (see Adriaensen et al 2019).…”
Section: Chagasmentioning
confidence: 99%
“…No que tange à educação, alguns estudos sobre programas de mentoria existentes em cursos de graduação e pós-graduação têm constatado os benefícios que esta relação traz, tanto para o mentor quanto para o mentorado, tais como, satisfação, produtividade, melhora das relações interpessoais, entre outros (Parker-Katz & Bay, 2008;Robnett et al, 2018;Adriaensen, Bijsmans, & Groen, 2019;Byrnes Junior et al, 2019;Lachenaye et al, 2019;& Ong et al, 2019).…”
Section: Startupsunclassified
“…Alguns estudos têm comprovado a eficácia da mentoria acadêmica realizada para o desenvolvimento de competências de pesquisa em alunos de pós-graduação (Robnett et al, 2018;Byrnes Junior et al, 2019), para o desenvolvimento de competências gerais em estudantes participantes da metodologia de aprendizagem baseada em problemas (PBL) (Adriaensen, Bijsmans, & Groen, 2019), para o desenvolvimento de competências técnicas e de pesquisa em estudantes de medicina (Ong et al, 2019) A mentoria eficaz tem sido associada a taxas de sucesso crescentes (Khan & Gogos, 2013;Pinto Zipp, Cahill, & Clark, 2009), aumentando as taxas de retenção (Khan & Gogos, 2013;Mason, 2012), e ajudando a inserir os alunos na comunidade acadêmica (Curtin, Malley, & Stewart, 2016;Gardner, 2008), enquanto a mentoria ineficaz pode ter efeitos opostos (Jones, 2013). O estudo de Lachenaye et al (2019) apresenta a avaliação de um processo de mentoria por pares, realizado no treinamento de novos profissionais, e que trouxe um maior senso de pertencimento entre os participantes, especialmente em temas semelhantes de sua formação, proporcionando uma maior abertura para o compartilhamento de dificuldades e busca de aprendizados.…”
Section: )unclassified
“…There is a significant focus in the literature on students' employability and career development learning (see Jackson, 2014a, b; Molseed et al , 2003; Pitan, 2016; Schlesinger and Daley, 2016; Shearer, 2009). In this regard, the generic skills are often considered of higher value than theoretical knowledge for a smooth transition from education to the labour markets (Adriaensen et al , 2019). This implies that next to the specialized knowledge and skills, generic skills are also essential for successful and innovative application of disciplinary knowledge in the workplace (Jackson and Chapman, 2012; Jackson, 2014a).…”
Section: Introductionmentioning
confidence: 99%